2013
DOI: 10.1002/jmri.24164
|View full text |Cite
|
Sign up to set email alerts
|

Presence of a hypovascular hepatic nodule showing hypointensity on hepatocyte‐phase image is a risk factor for hypervascular hepatocellular carcinoma

Abstract: Patients with chronic liver disease showing a hypointense hypovascular nodule in the liver on hepatocyte-phase EOB-MRI have a high risk of HCC development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 26 publications
1
22
0
Order By: Relevance
“…In contrast to other types of early cancer (4,5), multicentric hepatocarcinogenesis in the remnant liver could not be avoided after surgery in patients with early HCC, and half of the patients who underwent liver resection for early HCC had recurrence within 4 years. Consistent with our data, previous studies have reported that the presence of hypovascular nodules at resection for hypervascular HCC is a risk factor for postoperative recurrence, which may be mainly ascribed to multicentric hepatocarcinogenesis (11,22). Furthermore,~40% of second primary HCCs arising after resection of early HCCs could not be treated curatively, and the development of a second primary HCC was an important prognostic factor, which supports our contention that treatment of early HCC did not beneficially alter the prognosis of patients and is not necessarily required immediately (8).…”
Section: Discussionsupporting
confidence: 81%
“…In contrast to other types of early cancer (4,5), multicentric hepatocarcinogenesis in the remnant liver could not be avoided after surgery in patients with early HCC, and half of the patients who underwent liver resection for early HCC had recurrence within 4 years. Consistent with our data, previous studies have reported that the presence of hypovascular nodules at resection for hypervascular HCC is a risk factor for postoperative recurrence, which may be mainly ascribed to multicentric hepatocarcinogenesis (11,22). Furthermore,~40% of second primary HCCs arising after resection of early HCCs could not be treated curatively, and the development of a second primary HCC was an important prognostic factor, which supports our contention that treatment of early HCC did not beneficially alter the prognosis of patients and is not necessarily required immediately (8).…”
Section: Discussionsupporting
confidence: 81%
“…In addition, our results are also similar to the results of a previous study by Yamamoto et al [52], which reported that approximately one third of newly developed hypervascular HCCs showed presence of a high-risk nodule before hypervascularization on serial gadoxetic acid-enhanced MRI. Therefore, based on our study results as well as other previous study results [49,50,51,53], we believe that as a significant percentage of non-hypervascular HBP hypointense cirrhotic nodules turn out to be pathologically HCC and will likely develop malignant imaging features on serial radiologic evaluation, these non-hypervascular HBP hypointense cirrhotic nodules need to be considered as being suspicious for malignancy or having malignant potential even though they are hypovascular.…”
Section: Discussionmentioning
confidence: 92%
“…On the other hand, nonenhanced lesions in the arterial phase or hypervascular nodules without washout in the portal phase are found during the follow-up period in patients with high risk of hepatocarcinogenesis (2)(3)(4). The frequency of diagnosis of such nodules has increased since gadoxetic acidenhanced MRI has become clinically available (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%